HUBUNGAN TERPAAN INFORMASI TENTANG ETIKA DIGITAL DAN KOMPETENSI DIGITAL TERHADAP PERILAKU BERMEDIA SOSIAL - Hanan Hauzan, Muhammad; Naryoso, Agus; Setyabudi, Djoko (Interaksi Online, 2024)
This study aims to identify and explain the relationship between exposure to information on digital ethics and digital competence on social media behavior. The method used is a quantitative explanatory approach with a population of individuals participating in the "Indonesia Makin Cakap Digital" program through event.literasidigital.id and who are social media users. The results indicate that exposure to information on digital ethics and social media behavior have a significant relationship, with a very weak and positive correlation. Based on the research findings, it can be concluded that exposure to information on digital ethics is a more important factor influencing social media behavior compared to digital competence. Therefore, Indonesia needs to implement digital ethics development programs to enhance positive behavior on social media.